Imagens profanas na sagrada mídia? Imagens sagradas na mídia profana? algumas reflexões a respeito da televisão católica no Brasil - Araújo, Marlson Assis de (2012)
and Theology, this paper entitled Profane images in sacred media? Sacred images in profane media? Reflections on Catholic Television in Brazil approaches the four main Catholic television channels in Brazil: Rede Vida, Canção Nova, Século 21 and Aparecida. The research goes deep into the ambivalence of sacredness within the communication process between people and gods, as well as the path formed between Eletronic Church and mediatized sacredness. We shall systematize the history of these television channels, identify the mediatic environments which they manage, organize their Ecclesiastic typology, and focus on the religious quarrels surrounding the images and the significant moments of the institution in its relations with the media. This research tackles the consequent relation between media and religion, parting from the four analyzed television stations; the central issue being: which are the semiotic interferences and contaminations between the sacred and the media, both of which are very powerful fields? And what sort of medium is emerging from this devouring of the sacred, which is being transmitted by it? The research works with the concepts of sacred, profane, second reality, secularization, electronic church, mediatization, Church models, media environments, images, iconophagy, and scale of abstraction. Critical reference is supported by authors of the fields of Religious Studies (Rudolf Otto, Mircea Eliade, Émile Durkheim, Giorgio Agamben, Olivier Bobineau, Tank-Storper, Pierre Bourdieu, Peter Berger, Hervieu-Léger, Brenda Carranza) and mostly from Culture and Media Semiotics (Ivan Bystrina, Harry Pross, Vilém Flusser, Dietmar Kamper, Hans Belting, Christoph Wulf, Günter Anders, Aby Warburg, Edgar Morin, Norval Baitello, Alberto Klein, Muniz Sodré, Fausto Neto, Pedro Gomes, Joana Puntel) and Theology (Hugo Assmann, Libanio, Antônio de Almeida, John Fuellenbach, Leonardo Boff). The novelty of this research lies on two aspects: (1) interdisciplinary studies, since the fields of communications and religion require different, multiple, and complementary epistemological viewpoints; (2) reflections on Catholic Television in the perspective of culture semiotics and media and image semiotics in its analysis of the challenges the Churches and religions are required to face due to their mediatic urges. The alliance of media and religion is not immune to consequences